An Unusual Disorder Involving the Central Nervous System and the Thorax. Issue 6 (November 2016) - Panse, Prasad M.; Jensen, Eric A.; Cummings, Kristopher W.; Jokerst, Clinton E.; Swanson, Karen L.; Gotway, Michael B.
Abstract : The fact that the thorax is occasionally involved in disorders primarily presenting in extrathoracic locations often prompts screening chest imaging studies for asymptomatic patients. A number of disorders primarily presenting outside the thorax may have subclinical thoracic involvement, including various malignancies and noninfectious inflammatory disorders, such as sarcoidosis and connective tissue diseases. Among the rarest causes for asymptomatic thoracic involvement in the context of a primarily extrathoracic disorder is the Rosai-Dorfman disease. Rosai-Dorfman disease is a rare, nonmalignant polyclonal disorder of histiocytes, primarily occurring in lymph node sinuses and the extranodal lymphatic tissue, typically affecting young individuals. The disorder is idiopathic, although various etiologies, including an infectious origin and an autoimmune etiology, have been proposed. The histopathologic features of Rosai-Dorfman disease include emperipolesis (the presence of intact cells within the cytoplasm of other cells, commonly histiocytes in this context) and positive histiocytic cell surface staining for S-100, CD68, CD14, and CD15, with absent staining for factor XIIIa and MHC-2. Rosai-Dorfman disease commonly presents as painless cervical lymphadenopathy. The thorax may be more commonly affected than previously recognized, manifesting as peribronchial and/or mediastinal lymphadenopathy, with tracheal lesions, interstitial infiltration, and pleural disease possible, but uncommon. The diagnosis of Rosai-Dorfman disease typically rests on the recognition of the typical clinical presentation coupled with histopathologic analysis of the affected tissue. Treatment is often not required, and the disease occasionally remits spontaneously. When therapy is required, corticosteroid treatment is typically used, with immunosuppression used for more refractory cases. The prognosis of Rosai-Dorfman disease overall is good.